Hermeneutics and method : the 'universal viewpoint' in Bernard Lonergan - Coelho, Ivo (Lonergan studies., 2001)
Bernard Lonergan's notion of the 'universal viewpoint' is at once a timely and an unpopular topic. The very term seems to violate the postmodern concern for indigenous contexts, and yet, given the development of information technologies, world courts and international charters of rights, the need for universal frameworks has never been greater. This study by Ivo Coelho shows Lonergan's approach to be a complex blend of dialectic and dialogue that has much to offer to a discourse on transcultural issues.Coelho shows Lonergan's universal viewpoint to be an important hermeneutical tool that makes its appearance in "Insight" but is seemingly forgotten in the later works. He argues, however, that the notion did not disappear, but rather underwent a shift. Using the Thomist notion of wisdom (appropriated by Lonergan in his "Verbum" articles) as a key for interpretation, Coelho traces the flowering of the universal viewpoint into a mature theological method - one that holds out the hope of an effective transcultural mediation of meanings and values. Lonergan's approach to mediation, says Coelho, neither compromises on the demands of truth nor neglects the very real claims of difference.